Extracorporal modified ascitic fluid reinfusion in treatment of resistant ascites in liver cirrhosis - I. E. Onnintsev; S. Ya. Ivanusa; A. V. Khokhlov; A. A. Sokolov; A. V. Yankovskiy (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. The aim of the study was to estimate the efficacy of new method of reinfusion of extracorporeal modified ascitic fluid in therapy of diuretic resistance ascites in patients with liver cirrhosis and portal hypertension syndrome. MATERIAL AND METHODS. An analysis of treatment was made in 83 patients, who underwent laparocentesis and ascitic fluid evacuation. The patients were divided into two groups. Laparocentesis and fractional evacuation of ascitic fluid were carried out for the patients of the first group (n=40). This procedure was followed by intravenous infusion of 25 % albumin (10 g of albumin on each 2 litres of removed fluid) in order to make up losses of protein. Laparocentesis and ascitic fluid evacuation with following extracorporal processing and reinfusion were performed for the second group of patients (n=43). RESULTS. There was noted an increase of day diuresis from (620,0 ± 110,0) ml to (2,2 ± 0,4) l compared with the first group from (780 ± 80) ml to (1,2 ± 0,5) l and rise of sodium excretion (132 ± 7) mmol/l compared with the first group - (120 ± 6) mmol/l. An average molecular peptide concentration was decreased in blood plasma to (0,254 ± 0,098) units in the second group and it counted (0,298 ± 0,045) units in the first group. CONCLUSIONS. Reinfusion of extracorporeal modified ascitic fluid was more effective than conventional correction of albumin level and electrolytes disturbances against a background of ascitic fluid evacuation.